Use of critically important antimicrobial classes early in life may adversely impact bacterial resistance profiles during adult years: potential co-selection for plasmid-borne fluoroquinolone and macrolide resistance via extended-spectrum beta-lactam use in dairy cattle (2020)
The transfer of antimicrobial resistance genes commonly occurs via vertical and horizontal gene transfer, as such genes are often found on the same mobile genetic element. This occurrence can lead to the co‐selection of resistance to antimicrobials without their application. Dairy cattle located in the south‐western United States were enrolled in a matched‐pair longitudinal study to evaluate the effects of a two‐dose ceftiofur treatment for metritis on levels of third‐generation cephalosporin resistance among faecal Escherichia coli temporally. Escherichia coli chosen for further investigation were isolated on selective media, harboured extended‐spectrum beta‐lactam, fluoroquinolone and macrolide resistance genes. This combination has previously been unreported; importantly, it included genes encoding for resistance to antibiotics that can only be used in dairy cattle less than 20 months of age. Fluoroquinolones, macrolides and third and higher generation cephalosporins are considered critically important and highest priority for human medicine by the World Health Organization.